Relações emergentes e comportamento alimentar: uma investigação pelo método de escolha de acordo com o modelo - Viana, Renato Camargos (2006)
The study of the obesity was influenced by several fields among the health sciences, such as the Behavior Analysis. The current literature on Behavior Analysis points to a large range of approaches and interventions over the alimentary behavior control, including procedures for stimulus control and eating behavior control. Nevertheless, new research paradigms have been of importance to the study of complex behavior. Among these, there is the stimulus equivalence paradigm, a promising approach to understand the emergent behavior. The aim of this study was to investigate the emergence of equivalence relations by using a stimulus equivalence procedure. This included the use of food pictures and adjectives indicating low and high palatability in groups with different weight. Three studies were done. On the first one, 16 subjects eight with the IMC below 25 and eight with the IMC over 35 - were submitted to a conditional training to the relation AB (A1- sweet, A2-meat, A3-salad, B1-TUJ, B2-ZIM, B3-KAB) by using a matching-to-sample procedure, followed by a conditional training to the relation BC (B1-TUJ, B2-ZIM, B3- KAB, C1-adjective indicating high palatability, C2-another adjective indicating high palatability, C3-adjective indicating low palatability). Relations of Symmetry (BA and CB), Transitivity (AC) and combined Symmetry and Transitivity (Equivalence, CA) were then tested. On the second study, 16 new subjects were grouped following the same weight parameters and they were submitted to new phases of training and tests, including a different combination of stimuli of group C (C1-adjective indicating high palatability, C2- adjective indicating low palatability, C3-another indicating high palatability). A new sample of subjects was selected following the criteria that had been previously used, and submitted to a third procedure, using another combination of stimulus of the group C (C1- adjective indicating low palatability, C2-adjective indicating high palatability, C3-another adjective indicating high palatability). The results indicated that emergence of equivalence relations occurred in all of the procedures, and in most of the testing opportunities. No consistent differences were seen when the subjects with the IMC under 25 and over 35 were compared, or when the different procedures were used. However, subjects with the IMC over 35 required a more intensive training for the relations AB, when compared to subjects with the IMC under 25. This was directly correlated to age and may be because younger subjects are probably more familiar to electronic equipments